Superlattice nanostructures based on chalcogenide semiconductors - Sipatov (Functional Materials, 2009)
The multilayer chalcogenide semiconductor films with large layer lattice misfit (0.5-13 %) are shown to open the new opportunities for development of one-, two- and three-dimensional superlattice nanostructures. The superconductivity has been revealed for the first time in two-dimensional (dislocational) superlattices, the presence of periodic networks of misfit dislocations at interfaces being directly responsible for the superconductivity. The spectra of 1 uminescence from quantum dots have been discovered for the first time in three-dimensional PbSe-PbS superlattices, the dots being formed by structure modulations from periodic misfit dislocations along the layer interfaces and composition modulations in the orthogonal direction. The resonance tunneling of electrons via ferromagnetic EuS barriers was found for one-dimensional (compositional) superlattices. The antiferromagnetic interlayer coupling of magnetic EuS layers via non-magnetic PbS and YbSe spacers has been found for the first time in semiconductor superlattices. Such coupling is observed for unusual wide range of spacer thicknesses for narrow-gap PbS semiconductor (from 0.4 nm to 40 nm) and wide-gap YbSe (from 1 nm to 3 nm).